'Having a go'. (2nd January 2020) - Rawstrone, Annette
Abstract : 'Playing and exploring' focuses on how your child is engaging in what they are investigating and experiencing firsthand. Support your child to develop these important 'soft skills' that will put them on the path to becoming a lifelong learner.